The food crisis isn’t over - von Braun, Joachim (Springer, 2008)
Just a few months ago, the ‘crisis’ on everyone’s mind was the spike in food prices. Then the financial crisis gripped the world, food prices declined somewhat, and agricultural concerns lost their sense of immediacy. But we should not be complacent. The credit crunch is likely to have strong and long-lasting effects on emerging economies and on the people most in need. Between 2005 and summer 2008, the international prices of wheat and maize (corn) tripled, and that of rice grew fivefold. Poor people typically spend 50–70% of their income on food, and their wages did not adjust quickly enough to compensate for their shrinking purchasing power. From 2003–05 to 2007, the number of undernourished people increased from some 848 million to 923 million, largely because of the food-price crisis1. The worldwide credit crunch has let some air out of the commodity price bubble, providing a little relief — cereal prices have fallen by about 30–40% in recent months. But recession also threatens to cut the income and employment of the most vulnerable and undermine investment in agricultural production. The economic bailout and suggested market regulations now being discussed will not protect food prices from future spikes. The world’s food worries are by no means over.